2015
DOI: 10.1002/hipo.22534
|View full text |Cite
|
Sign up to set email alerts
|

Rapid memory stabilization by transient theta coherence in the human medial temporal lobe

Abstract: Presenting stimuli again after presentation of intervening stimuli improves their retention, an effect known as the spacing effect. However, using event-related potentials (ERPs), we had observed that immediate, in comparison to spaced, repetition of pictures induced a positive frontal potential at 200-300 ms. This potential appeared to emanate from the left medial temporal lobe (MTL), a structure critical for memory consolidation. In this study, we tested the behavioral relevance of this signal and explored f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 45 publications
(60 reference statements)
3
16
0
Order By: Relevance
“…Thus, it appears that both MTLs (and hippocampi) are necessary to produce this signal. This result is compatible with a previous study of electrical coherence: during the processing of immediately repeated stimuli, the extended MTL of both sides, rather than only the left side, displayed increased connectivity in the theta frequency band with the rest of the brain (Theze et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Thus, it appears that both MTLs (and hippocampi) are necessary to produce this signal. This result is compatible with a previous study of electrical coherence: during the processing of immediately repeated stimuli, the extended MTL of both sides, rather than only the left side, displayed increased connectivity in the theta frequency band with the rest of the brain (Theze et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…First, amnesic patients with Wernicke-Korsakoff syndrome did not produce this signal (Nahum et al, 2015). Second, electric coherence of the MTL in response to immediately repeated stimuli in this period correlated with later recognition (Theze, Guggisberg, Nahum, & Schnider, 2016); stronger coherence predicted better recognition after 30 min. These studies suggest that early, transient activation of the MTL upon repetition of information held in STM is linked to encoding of information in LTM, possibly also to the SE.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Using a continuous recognition task, James, Morand, Bareellona‐Lehmann, Michel, and Schnider () found that immediate repetition of pictures transiently activated the MTL in this period. Subsequent studies not only confirmed the hippocampal provenance of this signal using depth electrodes (Nahum et al, ), but also indicated a memory‐protective effect (Thézé, Guggisberg, Nahum, & Schnider, ). Patients having amnesia due to Wernicke–Korsakoff disease (Nahum et al, ) or medial temporal stroke (Tautvydaitė et al, ) did not exhibit this signal.…”
Section: Introductionmentioning
confidence: 71%